2019
DOI: 10.3389/fpls.2018.01944
|View full text |Cite
|
Sign up to set email alerts
|

Plant Glutathione Transferases and Light

Abstract: The activity and expression of glutathione transferases (GSTs) depend on several less-known endogenous and well-described exogenous factors, such as the developmental stage, presence, and intensity of different stressors, as well as on the absence or presence and quality of light, which to date have received less attention. In this review, we focus on discussing the role of circadian rhythm, light quality, and intensity in the regulation of plant GSTs. Recent studies demonstrate that diurnal regulation can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 116 publications
(155 reference statements)
2
66
0
Order By: Relevance
“…It is widely accepted that GSTs orchestrate and fine tune plant adaptation and tolerance to environmental stresses, pathogenic attackers and the detoxification of toxic chemicals and metabolites [2,3,[6][7][8][9][10][11][12][13][14][15][16]. Conducting genetic screens to identify components of salt stress tolerance in Arabidopsis revealed that AtGSTU19 and AtGSTF9 can be important cytoplasmic proteins in salt stress responses [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that GSTs orchestrate and fine tune plant adaptation and tolerance to environmental stresses, pathogenic attackers and the detoxification of toxic chemicals and metabolites [2,3,[6][7][8][9][10][11][12][13][14][15][16]. Conducting genetic screens to identify components of salt stress tolerance in Arabidopsis revealed that AtGSTU19 and AtGSTF9 can be important cytoplasmic proteins in salt stress responses [17].…”
Section: Introductionmentioning
confidence: 99%
“…The other key enzyme, which plays a role in the detoxification of various xenobiotics is the glutathione S-transferase (GST) [32]. GST activity and glutathione (GSH) levels also display circadian-and light-dependent patterns with a maximum late in the light and early dark phase [32][33][34][35]. Therefore, the selected daytime or night-time, and the presence or absence of daylight can be fundamental in case of the herbicide application on crops and weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Plant glutathione transferases (GSTs) are also involved in the detoxification of a wide range of harmful compounds, including lipid peroxides, reactive aldehydes, and xenobiotics by the conjugation of GSH [71]. Plant GSTs consist of three superfamilies (cytosolic, mitochondrial, and microsomal) and can be further divided into distinct classes (e.g., tau, phi, theta, zeta, lambda), but the accurate function of mitochondrial GSTs remained unexplored [72,73].…”
Section: Mitochondria-associated Ros Metabolism and Non-ros Moleculesmentioning
confidence: 99%